The use of Chironomus riparius larvae to assess effects of pesticides from rice fields in adjacent freshwater ecosystems - Faria, Mafalda S.
A bioassay with Chironomus riparius larvae, using larval development and growth as endpoints, was carried out inside a rice field and in the adjacent wetland channel in Portugal, during pesticide treatments (molinate, endosulfan and propanil) to determine impact caused by pesticide contamination in freshwater ecosystems. The bioassay was also performed under laboratory conditions, to assess whether in situ and laboratory bioassays demonstrated comparable results. Growth was inhibited by concentrations of endosulfan (2.3 and 1.9 mu g L-1 averages) in water from rice field in both the field and laboratory, and by concentrations of endosulfan (0.55 and 0.76 mu g L-1 averages) in water from the wetland channel in the laboratory bioassay, while development was not affected. C riparius larvae were not affected by, molinate and propanil concentrations. The results indicate that endosulfan treatments in rice fields may cause an ecological impairment in adjacent freshwater ecosystems. The results also indicate that laboratory testing can be used to assess in situ toxicity caused by pesticide contamination. (c) 2006 Elsevier Inc. All rights reserved.